1998
DOI: 10.1111/j.1471-0528.1998.tb09356.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of women with chronic pelvic pain, chronic nonpelvic pain and those with no history of pain attending general practitioners

Abstract: Objective To investigate and compare the demographic and psychosocial profiles of women with chronic pelvic pain, chronic pain in a different site, and those with no history of pain with specific reference to a history of sexual abuse.Design A prospective comparative study.Setting Pelvic Pain Clinic at Leicester General Hospital NHS Trust, Pain Management Clinic at LeicesterRoyal Infirmary NHS Trust and two General Practices.Participants Thirty women with chronic pelvic pain, 30 women with chronic pain in a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(56 citation statements)
references
References 20 publications
4
48
0
4
Order By: Relevance
“…Apesar de que a síndrome de estresse pós-traumático e a síndrome do trauma do estupro são relativamente pouco freqüentes, outras seqüelas psicológicas se observam com muita freqüência e podem expressar-se de muitas formas: cefaléia crônica, fadiga, transtornos do sono, pesadelos e transtornos da apetite [60][61][62] . Vários estudos têm mostrado, ainda, que mulheres com história de violência sexual têm maior incidência de alterações menstruais, dor pélvica crônica, dispareunia e disfunções sexuais que aquelas que nunca sofreram esse tipo de violência 10,31,[63][64][65][66] .…”
Section: Característica Da Violência Sexualunclassified
“…Apesar de que a síndrome de estresse pós-traumático e a síndrome do trauma do estupro são relativamente pouco freqüentes, outras seqüelas psicológicas se observam com muita freqüência e podem expressar-se de muitas formas: cefaléia crônica, fadiga, transtornos do sono, pesadelos e transtornos da apetite [60][61][62] . Vários estudos têm mostrado, ainda, que mulheres com história de violência sexual têm maior incidência de alterações menstruais, dor pélvica crônica, dispareunia e disfunções sexuais que aquelas que nunca sofreram esse tipo de violência 10,31,[63][64][65][66] .…”
Section: Característica Da Violência Sexualunclassified
“…Several studies have shown an association between unexplained medical problems including pelvic pain [60,61], gastrointestinal disorders [62], general medical problems [63], and prior sexual abuse. Three reports of childhood abuse in women with FM found a high prevalence of lifetime sexual abuse ranging from 17% to 65% [64][65][66].…”
Section: Childhood Abuse and Fibromyalgiamentioning
confidence: 99%
“…Previous clinical studies have reported that chronic pain disorder may cause depression and markedly worsen the quality of life of the patient [9]. In addition, women with chronic pelvic pain could have a higher incidence of sexual abuse than women without the pain [10,11]. Taken together, the present investigation further implies that a suitable pharmacological therapy accompanying a psychological one-if necessary-could be crucial to treating chronic pelvic pain effectively.…”
Section: Discussionmentioning
confidence: 61%